2018
DOI: 10.31223/osf.io/cyuwn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the timing and nature of the multiple phases of slope instability on eastern Rockall Bank, Northeast Atlantic

Abstract: One of the most challenging tasks when studying large submarine landslides is determining whether the landslide was initiated as a single large event, a chain of events closely spaced in time or multiple events separated by long periods of time as all have implications in risk assessments. In this study we combine new multichannel seismic profiles and new sediment cores with bathymetric data to test whether the Rockall Bank Slide Complex, offshore western Ireland, is the composite of multiple slope collapse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Until recently, the RBSC had been considered as one single event mass flow [ 41 ]. New sedimentary and seismic data taken from the depositional lobes of the RBSC demonstrate that the RBSC morphology is the result of multiple phases of slope failure, at least three, that were separated by long periods of slope stability [ 42 ]. Radiocarbon dating showed that the most recent event took place 21 ka, which is 3000 years post Last Glacial Maximum (LGM), when the British Irish Ice Sheet (BIIS) was still at maximum extent and was only just starting to destabilize [ 42 ].…”
Section: Submarine Sliding In the Rockall Bank Slide Complexmentioning
confidence: 99%
See 4 more Smart Citations
“…Until recently, the RBSC had been considered as one single event mass flow [ 41 ]. New sedimentary and seismic data taken from the depositional lobes of the RBSC demonstrate that the RBSC morphology is the result of multiple phases of slope failure, at least three, that were separated by long periods of slope stability [ 42 ]. Radiocarbon dating showed that the most recent event took place 21 ka, which is 3000 years post Last Glacial Maximum (LGM), when the British Irish Ice Sheet (BIIS) was still at maximum extent and was only just starting to destabilize [ 42 ].…”
Section: Submarine Sliding In the Rockall Bank Slide Complexmentioning
confidence: 99%
“…New sedimentary and seismic data taken from the depositional lobes of the RBSC demonstrate that the RBSC morphology is the result of multiple phases of slope failure, at least three, that were separated by long periods of slope stability [ 42 ]. Radiocarbon dating showed that the most recent event took place 21 ka, which is 3000 years post Last Glacial Maximum (LGM), when the British Irish Ice Sheet (BIIS) was still at maximum extent and was only just starting to destabilize [ 42 ]. One hypothesis for the triggering mechanism suggests that sedimentation on the upper part of the slope enhanced by strong bottom current activity removed support from the base-of-slope, leading to slope instability and subsequently failure [ 35 , 41 ].…”
Section: Submarine Sliding In the Rockall Bank Slide Complexmentioning
confidence: 99%
See 3 more Smart Citations